The role of Ets2 transcription factor in the induction of microRNA-155 (miR-155) by lipopolysaccharide and its targeting by interleukin-10. - O'NEILL, LUKE (My University, 2014)
MicroRNA-155 (miR-155) is highly expressed in many cancers such as B cell lymphomas and myeloid leukemia and inflammatory disorders such as rheumatoid arthritis, atopic dermatitis, and multiple sclerosis. The role of miR-155 as both a promoter of inflammation and an oncogenic agent provides a clear need for miR-155 itself to be stringently regulated. We therefore investigated the transcriptional regulation of miR-155 in response to the respective pro- and anti-inflammatory mediators LPS and IL-10. Bioinformatic analysis revealed Ets binding sites on the miR-155 promoter, and we found that Ets2 is critical for miR-155 induction by LPS. Truncation and mutational analysis of the miR-155 promoter confirmed the role of the Ets2 binding site proximal to the transcription start site for LPS responsiveness. We observed increased binding of Ets2 to the miR-155 promoter and Ets2 deficient mice displayed decreased induction of miR-155 in response to LPS. IL-10 inhibited the induction of Ets2 mRNA and protein by LPS, thereby decreasing Ets2 function on the pri-155 promoter. We have thus identified Ets2 as a key novel regulator in both the positive and negative control of miR-155 in the inflammatory response.
PUBLISHED
Keywords: Biochemistry